A control algorithm for simulation of real-world operating conditions for the drivetrain of an all-wheel drive vehicle with individually driven wheels on a chassis dynamometer. Issue 1 (1st January 2020) - Gorelov, V.A.; Komissarov, A.I.; Sekletina, L.S.; Gartfelder, V.A.
Abstract: The article presents a new control algorithm for the simulation of real-world operating conditions for the drivetrain of an all-wheel drive transportation vehicle with individually driven wheels on a chassis dynamometer. The main idea of the algorithm is that the wheel torques and angular velocities on a chassis dynamometer are synchronized with the corresponding parameters obtained on a road. For the verification of the algorithm, the authors used mathematical models of an 8 × 8 vehicle with individually driven wheels on a chassis dynamometer and on a road. Wheel torques and angular velocities obtained by the simulation of the straight-line motion of the vehicle on a road with longitudinal slope were used for the control of the driving torques in the model of the chassis dynamometer. The simulation has proved capability of the proposed algorithm to reproduce dynamic loads in the drivetrain on a chassis dynamometer identical to the ones registered on a road.